Analisis Biaya Diferensial Sebagai Alat Pengambilan Keputusan Pada Kost Putri Candra Dewi Di Sendangwaru Kec.Pringapus - Warni Damai Putri Waruwu; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2024)
Financial planning is a crucial stage in business management that enables efficient fund allocation to achieve company goals. The significance of financial planning in preparing for the future of a business cannot be underestimated, as business success heavily relies on sound financial strategies. In this context, the analysis of differential costs becomes a crucial tool in business decision-making, especially when choosing between purchasing new items or reproducing old ones. This research utilizes a descriptive qualitative approach to describe and understand the cost comparison phenomenon between the purchase of new items and the reproduction of old items at Kost Putri Candra Dewi. Through cost analysis, it was found that purchasing new items has a higher price margin compared to reproducing old items, even though maintenance costs for old items tend to be higher. In conclusion, while purchasing new items may require a larger initial investment, in the long run, it can generate higher and more financially and operationally profitable margins.